KAJIAN MITIGASI BENCANA TANAH LONGSOR DI KABUPATEN BANJARNEGARA - Amni Zarkasyi Rahman (Departemen Administrasi Publik, Universitas Diponegoro, 2015)
All disasters experienced by Indonesia in the last years has developed anawareness of the fragility and vulnerability. At this time, the disastermanagement is currently insufficient anymore. The disaster management gain anew dimension with UU 24/ 2007 and followed some related regulations.Mitigation program implemented by BPBD Banjarnegara includes Structuraland Non Structural Mitigation has been completed well. For example, disasterdatabase, installation of Early Warning System (EWS), information andsocialization, training and disaster simulation.In the future, mitigation will be focused on public education. Thegovernment should implement the hazard maps, environmental improvement,evacuation route, installation of low-cost EWS at all location, and relocation. inadditon, whole villages must become village disaster response (desa tanggapbencana).Key words : landslides; structural mitigation; non structural mitigation.